Correlation Between English Learning Motivation And Public Speaking Ability - Taufiq Sholihin; Sabarun Sabarun; Sri Normuliati (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2023)
This study is intended to determine the extent of correlation between English learning motivation and public speaking ability. The design used is Correlation analysis by using Simple Linear Regression. The participants of the study were 30 students of English Education Study program of IAIN Palangka Raya who joined Speaking class and who used the questionnaire. The data were collected from 4 April to 8 May September 2023. The result of the study shows that the data above is stated to be correlated. Variable X to Variable Y has a correlation. With the degree of relationship, namely 0.70 and the form of the relationship is positive.